Overview On Implications Of Sustainable Development In Nursing Field: Brief Review (Journal of Pharmaceutical Negative Results, 2023)
Background: Sustainable development is a compound concept that has appeared because of the apprehension for the environment and increased a sustainable pathway of development in the 21st century. Even though health consequences have better in low-income and middle-income countries (LMICs) in the past few decades. Fluctuating health needs, increasing public hopes, and determined new health goals are floating the bar for health systems to create better health consequences and better social significance . So, the nurse should be practice like chances as treating all patient similarly and pro-vided wholly patients with the available technologies that can donate to their recovering or health promotion with the intention of confirm patients security, safety, social and health through technologies such as good lighting, quality furniture and comfort areas. Aim : this a systemic brief review aims to highlight on the implications of Sustainable Development in Nursing field . Data search, review and collection: Done in relative to our paper topic from the year 2015- 2022 as Sustainable development, , Nursing Practice , Nursing Care , Health Care , Sustainable nursing strategies , Implications of sustainable development in nursing care Data is collected from reliable database searches from Qassim university digital library Saudi Digital Library ( SDL) search as Directory of open access journal , PubMed , and E-article Implications for clinical practice: There are an obvious needs for educate the nurse regarding strategies for sustainable development in nursing practice as usage of sterilized disposable items, waste management techniques and facilities. Additionally, there are obvious needs for instructional guidelines / information on sustainable development attitude in using all devices / machines and turn off if not needed as suction machine, monitor / computer / light and television.